Automedicación con aines guiada por padres y epigastralgia en estudiantes de la Escuela Daniel Rodas Bustamante Loja 2014 - Hidalgo Saavedra, Jorge Patricio (2015)
Self-medication is a problem related to a number of complications such as masking the disease, occurrence of adverse effects, prolongation or worsening of the disease, and drug addiction, so it is necessary to know how serious this problem in school ¨ Daniel Rodas Bustamante ¨ The study's main objective was to relate the self-medication with NSAIDs guided by parents with the onset of epigastric pain in children self-medicated by a quantitative, cross-sectional and correlational study, the study sample was 245 parents who met the criteria inclusion, to whom I apply the survey. Results: The (77.56%) of parents of family self-medicate their children, using two NSAIDs at (32.11%) cases in the three NSAIDs (28.42%). Used as drugs of choice Acid acetylsalicylic and Ibuprofen in (32.10%). The (37,37%) self-medication to their children twice a week, and (24.21%) twice a month. The (26.84%) of children who had epigastric pain were self-medicated . The (91.84%) of parents do not know the risks of using drugs. Finally, the results reveal that most of the parents self-medicate their children incorrectly why should spread the rational use of these and educate people for proper use. PASSWORDS: Self-medication, NSAIDs, Epigastralgia.